2013
DOI: 10.1189/jlb.0613312
|View full text |Cite
|
Sign up to set email alerts
|

At the Bench: Preclinical rationale for exploiting NK cells and γδ T lymphocytes for the treatment of high-risk leukemias

Abstract: NK cells and γδ T lymphocytes display potent cytolytic activity against leukemias and CMV-infected cells and are thus, promising immune effector cells in the context of allo-HSCT. NK cells express HLA class I-specific inhibitory receptors and preferentially kill HLA class I(low) tumors or virus-infected cells. Killing occurs upon engagement of activating NKRs with ligands that are up-regulated on tumors and infected cells. A similar activating receptor/ligand interaction strategy is used by γδ T cells, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 234 publications
0
36
0
Order By: Relevance
“…Innate immune cells, notably NK cells and gd T cells, are of particular interest on account of their ability to kill hematological 2,3 or solid tumor cells 4 without inducing GvHD. 5,6 The anti-leukemic role of gd T cells was suggested by a correlation between Vd1 T cells expansion and prognosis following AHSCT. 7,8 Aside from Vd1 T cells, Vg9Vd2 T cells, the main circulating subset, account for 1-10% of human T lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Innate immune cells, notably NK cells and gd T cells, are of particular interest on account of their ability to kill hematological 2,3 or solid tumor cells 4 without inducing GvHD. 5,6 The anti-leukemic role of gd T cells was suggested by a correlation between Vd1 T cells expansion and prognosis following AHSCT. 7,8 Aside from Vd1 T cells, Vg9Vd2 T cells, the main circulating subset, account for 1-10% of human T lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Two basic KIR haplotypes can be found in humans: the group A haplotype, which has a fixed number of genes encoding inhibitory receptors (with the exception of the activating receptor KIR2DS4), and the group B haplotypes, which have variable gene content and 1 or more of the B-specific genes: KIR2DS1, KIR2DS2, KIR2DS3, KIR2DS5, KIR2DL2, and KIR2DL5. 1,7,8 Among haplotype B individuals, a KIR B-content score can further be established 8 on the basis of the number of centromeric and telomeric KIR B haplotype motifs. Cooley et al recently reported a reduced relapse risk in adults with acute myeloid leukemia, but not in those with ALL, given allogeneic HSCT from unrelated KIR haplotype B donors.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have suggested beneficial roles of γδ T cells in the context of hematopoietic cell transplantation, reports of clinical experiences are still very limited. 6,[10][11][12][13][14][15] There have been several reports on HHCT in pediatric patients. 4,5,7,[16][17][18] In our current study, all 42 patients achieved stable engraftment early post transplant at a median of 10 days.…”
Section: Discussionmentioning
confidence: 99%